Rancang Bangun Sistem Penyiraman Tanaman Tomat Menggunakan Wireless Sensor Network dengan Metode Fuzzy Logic - Muhammad Aji Guna Darmawan; Adhitya Bhawiyuga; Sabriansyah Rizqika Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Farmers are one of the majority professions in Indonesia. Lately, the conditions in the agricultural sector are in decline. One of the problems is the damaged irrigation problem in Indonesia's agricultural areas and the method used is still conventional. Therefore, more modern technology is one of the solutions. Moreover, the agricultural sector is very promising as an application for testing technology. A plant monitoring system that can determine the environmental conditions of plants such as soil moisture conditions, air temperature, etc. Then a decision is made to use the fuzzy method in the form of plant watering according to the volume needed using a smartphone so that it can stabilize the plant conditions on agricultural land. The results of the research will show that the process of plant growth will be good so that agriculture is maximized and very useful for farmers.